The Interpersonal Communication Process - Amelia, Amelia; Sembiring, Ari Wibowo; Azzahra, Nindya; Tanjung, Laila Ali; Aswaruddin, Aswaruddin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Interpersonal communication is a scientific discipline that examines how individuals exchange messages, thoughts, and emotions, facilitating relationships and mutual understanding. This journal article explores how the interpersonal communication process works, with the research method being a literature review, collecting information from scientific journals, books, and credible online sources. The findings contribute to the development of new communication models, particularly in urban societies where diverse cultures and social norms complicate interactions. The study’s practical implications highlight the importance of improving social relationships by understanding the dynamics of communication, including how to adapt to modern challenges such as technology and multiculturalism. By providing insights into effective communication strategies, this research aims to enhance personal and professional interactions, conflict resolution, and community cohesion in the contemporary world.